Long‐term geomagnetically induced current observations in New Zealand: Earth return corrections and geomagnetic field driver. Issue 8 (5th August 2017) - Mac Manus, Daniel H.; Rodger, Craig J.; Dalzell, Michael; Thomson, Alan W. P.; Clilverd, Mark A.; Petersen, Tanja; Wolf, Moritz M.; Thomson, Neil R.; Divett, Tim
Abstract: Transpower New Zealand Limited has measured DC currents in transformer neutrals in the New Zealand electrical network at multiple South Island locations. Near‐continuous archived DC current data exist since 2001, starting with 12 different substations and expanding from 2009 to include 17 substations. From 2001 to 2015 up to 58 individual transformers were simultaneously monitored. Primarily, the measurements were intended to monitor the impact of the high‐voltage DC system linking the North and South Islands when it is operating in "Earth return" mode. However, after correcting for Earth return operation, as described here, the New Zealand measurements provide an unusually long and spatially detailed set of geomagnetically induced current (GIC) measurements. We examine the peak GIC magnitudes observed from these observations during two large geomagnetic storms on 6 November 2001 and 2 October 2013. Currents of 30–50 A are observed, depending on the measurement location. There are large spatial variations in the GIC observations over comparatively small distances, which likely depend upon network layout and ground conductivity. We then go on to examine the GIC in transformers throughout the South Island during more than 151 h of geomagnetic storm conditions. We compare the GIC to the various magnitude and rate of change components of the magnetic field. Our results show that there is a strong correlation between the magnitude of the GIC and the rate of change of the horizontal magnetic field ( H′ ). This correlation is particularly clear for transformers that show large GIC current during magnetic storms. Key Points: From 2001 to 2015 DC measurements were made in up to 58 distinct transformers in South Island, NZ Stray HVDC Earth return currents and calibration problems have been corrected to produce a GIC data set H prime is the best correlated driver of observed GIC magnitude but not for every storm in every location